2009
DOI: 10.2340/16501977-0320
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a functional electrical stimulation-assisted leg-cycling wheelchair on reducing spasticity of patients after stroke

Abstract: Leg spasticity is reduced after short-term propulsion of the FES-LW and LW. The application of FES has an additional effect on reducing spasticity in subjects with higher muscle tone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…The findings of the present study agree with previous studies [20][21][22]. Motl et al [21], reported that H reflex of soleus was significantly suppressed after one bout of cycling exercise for normal subjects and subjects with multiple sclerosis.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…The findings of the present study agree with previous studies [20][21][22]. Motl et al [21], reported that H reflex of soleus was significantly suppressed after one bout of cycling exercise for normal subjects and subjects with multiple sclerosis.…”
Section: Discussionsupporting
confidence: 95%
“…Lo et al [20], found there was a significant decrease in muscle tone among higher muscle tone subjects in the cycling with FES group. In the present study, we also found a significant difference in cH/M among the higher muscle tone groups from both FES-CG and CG groups.…”
Section: Discussionmentioning
confidence: 97%
“…Measurement of the H-reflex has been used as an assessment of the nervous system for various neuromuscular diseases (Bakheit et al, 2003;Hodapp et al, 2009;Knikou et al, 2009;Lo et al, 2009;Phadke et al, 2007;Stewart et al, 2004;Trimble et al, 2001), as well as for the assessment of diverse therapeutic interventions, such as surgeries, medications, therapeutic modalities, and exercise training (Palmieri et al, 2004). As an example, Trimble et al reported that the amplitude of the soleus H-reflex of persons with incomplete spinal cord injury decreased after training (Trimble et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Apkarian and Naumann performed a similar set of experiments and also measured reciprocal inhibition of triceps surae during stimulation of the peroneal nerve [66]. Unlike Thompson Interestingly, Lo et al [67], Krause et al [68], and Van der Salm et al [69] describe decreased tone from electrical stimulation of spastic muscles themselves, rather than their antagonists, in spastic stroke and SCI patients. Van der Salm et al noted that while this could be secondary to recurrent inhibition from Renshaw cells, nonneurogenic factors could also be at play, including local blood flow or mechanical factors [69].…”
Section: Combined Functional Electrical Stimulation And Botulinum Tomentioning
confidence: 99%